Pengaruh pemberian Rumput Lapangan (Paspalum conjugatum) dan daun Lamtoro Gung (Leucaena leocochepala) terhadap bobot karkas kelinci lokal jantan (Erictolagus cuniculus). - Kastalani Kastalani (Fakultas Peternakan Universitas Kristen Palangka Raya, 2015)
This study aims to determine the effect of field grass and lamtoro gung leaves on the feed consumption of local hare male. The experiment using completely randomized design (CRD), with five treatments and four replications. The result showed that with using field grass and lamtoro gung leaves would significant effect on the carcass weight. Key words : Erictolagus cuniculus, local hare male, field grass, lamtoro gung leaves, carcass weight.